Effect of Venture Capital Financing on Investment in Kenya - Wanjala, Kevin; Kizito, Valerie (Business Perspective Review, 2020)
Purpose: The objective of this paper is to determine the effect of venture capital financing on investment in Kenya. Methodology: To achieve the objective of the study, venture capital was disaggregated into two variables, namely, the number of firms financed and the total amount of financing. Other variables, such as interest rate and GDP per capita were also included in the analysis to act as control variables. The study used 10 years of data spanning from 2009 to 2018. A regression analysis was done in order to analyze the data. Results: The study established that there is a positive correlation between the number of firms financed and the aggregate investment in Kenya. The study observed that the total amount of financing has a positive correlation with aggregate investment. Implications: The study concludes that venture capital financing has a positive effect on aggregate investment levels in Kenya. The study recommends that the Kenyan government should come up with ways of financing small and medium enterprises, which will boost their productive capacities leading to more investment in the country and more generation of income.